Application of the Matlab® Linprog function to plan the short term operation of hydro stations considered as price makers - João Tomé Saraiva (2016)
The restructuring of power systems induced newchallenges to generation companies in terms of adequatelyplanning the operation of power stations in order to maximizetheir profits. In this scope, hydro resources are becomingextremely valuable given the revenues that their operation cangenerate. In this paper we describe the application of theMatlab® Linprog optimization function to solve the Short TermHydro Scheduling Problem, HSP, admitting that some stationsare installed in the same cascade and that some of them havepumping capabilities. The optimization module to solve the HSPproblem is then integrated in an iterative process to take intoaccount the impact that the operation decisions regarding thehydro stations under analysis have on the market prices. Theupdated market prices are then used to run again the HSPproblem thus enabling considering the hydro stations as pricemakers. The developed approach is illustrated using a systembased on the Portuguese Douro River cascade that includes 9hydro stations (4 of them are pumping stations) and a totalinstalled capacity of 1485 MW.